Effect of CaCo3 Particulate Filler on the Mechanical Properties of Surface Modified Coir Fibre/Epoxy Composite. Issue 1 (December 2020) - Vijaya Rajan, V; Shanmugam, M; Santhanam, V; Ramkumar, S
Abstract: In this work, the effect of Calcium Carbonate (CaCo3 ) particulate filler on the mechanical properties of the coir fibre/Epoxy composites was studied. Calcium Carbonate was incorporated with Coir/Epoxy at different weight percentages such as 4%, 8%, 12%, 16% and 20%. Composite specimens were fabricated by incorporating surface-treated coir fibre at 15% fibre loading and powdered Calcium carbonate. Coir fibres were treated by 2% NaOH solution to improve the surface adhesion. Hand layup method was employed to fabricate the composite samples. As per ASTM standards mechanical properties were evaluated on specimens. The results indicated that the addition of CaCo3 on coir fibre/epoxy resin up to 16% filler loading could improve the tensile, flexural and impact strength. The mechanical properties were reduced by adding more than 16% of CaCo3 filler to the composites. The test results indicated a marginal increase in mechanical strengths and a relatively significant improvement in the mechanical moduli. SEM images of the tensile test samples were taken to study the surface morphology.